The Statistical Fragility of Operative vs Nonoperative Management for Achilles Tendon Rupture: A Systematic Review of Comparative Studies. (October 2022) - Fackler, Nathan P.; Karasavvidis, Theofilos; Ehlers, Cooper B.; Callan, Kylie T.; Lai, Wilson C.; Parisien, Robert L.; Wang, Dean
Background: The statistical significance of randomized controlled trials (RCTs) and comparative studies is often conveyed utilizing the P value. However, P values are an imperfect measure and may be vulnerable to a small number of outcome reversals to alter statistical significance. The interpretation of the statistical strength of these studies may be aided by the inclusion of a Fragility Index (FI) and Fragility Quotient (FQ). This study examines the statistical stability of studies comparing operative vs nonoperative management for Achilles tendon rupture. Methods: A systematic search was performed of 10 orthopaedic journals between 2000 and 2021 for comparative studies focusing on management of Achilles tendon rupture reporting dichotomous outcome measures. FI for each outcome was determined by the number of event reversals necessary to alter significance ( P < .05). FQ was calculated by dividing the FI by the respective sample size. Additional subgroup analyses were performed. Results: Of 8020 studies screened, 1062 met initial search criteria with 17 comparative studies ultimately included for analysis, 10 of which were RCTs. A total of 40 outcomes were examined. Overall, the median FI was 2.5 (interquartile range [IQR] 2-4), the mean FI was 2.90 (±1.58), the median FQ was 0.032 (IQR 0.012-0.069), and the mean FQ was 0.049 (±0.062). The FI was less than the number of patients lost to follow-up for 78% of outcomes. Conclusion: Studies examining the efficacy of operative vs nonoperative management of Achilles tendon rupture may not be as statistically stable as previously thought. The average number of outcome reversals needed to alter the significance of a given study was 2.90. Future analyses may benefit from the inclusion of a fragility index and a fragility quotient in their statistical analyses.